Heart Failure, Palliative Care and Nursing: an integrative literature review (Research, Society and Development, 2023)
Objective: To understand what the current scientific literature reveals about palliative care in the context of heart failure and the work of nursing with application in the scope of hospital care or specialized in palliative care in the world. Methodology: Integrative literature review according to Whittemore and Knafl's definitions, with content analysis according to Laurence Bardin's theory for qualitative studies, using the Virtual Health Library portal, selecting 19 articles published in the last 05 years in relation to the research proposal and context. Results: Four central categories emerged in the Material Exploration stage, which were broken down in the Treatment of Results as “The Relationship between Palliative Care and the Treatment of Heart Failure”; “Identification of Palliative Care needs in Heart Failure”; “Integrating Palliative Care in the Context of Heart Failure” and “The Role of Nursing on Heart Failure in Palliative Care”. Conclusion of the study: Only two studies were found referring to the role of nursing in heart failure, which highlights the scarcity of studies that address the role of nurses and nursing staff in palliative care in heart failure. The literature addresses the importance of timely initiation of palliative care in the context of heart failure as opposed to current challenges for its implementation, pointing out clinical tools as aids in overcoming barriers encountered in practice in hospitals and specialized in palliative care in the world.